2008
DOI: 10.2137/145960606779216263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactic acid bacteria inoculants, formic acid, potassium sorbate and sodium benzoate on fermentation quality and aerobic stability of wilted grass silage

Abstract: The efficiency of a novel strain of lactic acid bacteria inoculant (Lactobacillus plantarum VTT E-78076, E76) on the fermentation quality of wilted silage was studied. Furthermore, the possibility to improve aerobic stability of silages by combining an inoculant and chemical preservatives was investigated. Two experiments were conducted with wilted timothy-meadow fescue herbage (dry matter 429 and 344 g kg -1 ) using six treatments. In experiment I, E76 (10 6 cfu g -1 fresh matter (FM)) was applied alone and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
4
12
0
1
Order By: Relevance
“…This result is in agreement with that of Saarisalo et al (2006). Formic acid is effective in inhibiting amino acid breakdown during ensilage process as reflected by the lowest level of N-NH 3 in the silage supplemented with formic acid especially at the level of 7.5% FA.…”
Section: Discussion Experiments 1: Fermentative Quality Of Napier Grassupporting
confidence: 91%
See 3 more Smart Citations
“…This result is in agreement with that of Saarisalo et al (2006). Formic acid is effective in inhibiting amino acid breakdown during ensilage process as reflected by the lowest level of N-NH 3 in the silage supplemented with formic acid especially at the level of 7.5% FA.…”
Section: Discussion Experiments 1: Fermentative Quality Of Napier Grassupporting
confidence: 91%
“…Formic acid was able to restrict fermentation indirectly by limiting the activity of LAB to produce lactic acid. The result was consistent with that reported by Saarisalo et al (2006), but different from that reported by Aksu et al (2006) that formic acid supplementation did not alter lactid acid concentration. These results suggest that the effects of formic acid on lactid acid concentration are inconsistent.…”
Section: Experiments 2 Chemical and Microbiological Qualities And Insupporting
confidence: 87%
See 2 more Smart Citations
“…Jaakkola et al (2010) observed that the combination of L. plantarum with sodium benzoate was more efficient than the combination of L. plantarum and L. buchneri. In the experiment of Saarisalo et al (2006b) the aerobic stability of silages was increased by inoculation with L. plantarum and was distinctly increased by treatment with L. plantarum in combination with sodium benzoate compared with untreated silage. Some inoculant lactic acid bacteria strains produce anti-microbial compounds that inhibit mould growth or undesirable bacterial species like Salmonella sp., Listeria sp.…”
Section: Discussionmentioning
confidence: 97%